Low voltage protection method of DFIG based on rotor-side double current limiting circuit - Yang, Hongyu; ZHU, Yi; Yuan, Chao; Liu, Yanan; Mei, Rui; LI, Zhenxing (Frontiers in Energy Research, 2023)
A doubly fed induction generator (DFIG) configured for crowbar protection faces the following problems during low voltage ride through (LVRT): delayed input of crowbar protection and the difficulty in coordinating current limiting targets and DC voltage overrun with constant resistance rectification. A low voltage protection method of a DFIG based on a rotor-side double current limiting circuit is proposed. The rotor current characteristics during a fault are analyzed from a time domain perspective and used as a basis for resistance setting. The transient response characteristics of a resistive superconducting fault current limiter (RSFCL) are used for fast initial suppression of rotor currents. The adaptive crowbar resistance adjustment method is used to realize the coordinated consideration of current limiting and DC voltage non-overrun. The simulation results show that the proposed protection method effectively shortens the actual input time of the current limiting circuit and has good suppression ability for the rotor current at the early stage of fault. The adaptive and flexible resistance setting of the controllable crowbar circuit ensures that the DC voltage does not exceed the limit during the fault current limiting period, which helps improve the LVRT capability of doubly fed wind turbines.